The Fur Country: Or, Seventy Degrees North Latitude - Verne, Jules, 1828-1905; D'Anvers, N., 1844-1933 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Fur Country: Or, Seventy Degrees North Latitude" by Jules Verne is a novel written during the late 19th century that delves into the exploration and adventure in the Arctic regions. The story centers around Lieutenant Jaspar Hobson and his team as they embark on a perilous journey to establish a new fort in the fur-rich territories north of the Hudson Bay. The narrative immerses readers into the harsh realities of Arctic exploration, highlighting the struggles against unforgiving weather and the challenges of survival in a landscape scattered with wildlife yet fraught with danger. At the start of the novel, the story unfolds at Fort Reliance during a soirée hosted by Captain Craventy, setting the stage for the expedition. Various characters are introduced, including Paulina Barnett, a determined traveler who joins the expedition, and Sergeant Long, a steadfast soldier. The chapter sets a festive yet cold atmosphere, contrasting the warmth of human camaraderie with the severe Arctic conditions outside. As the preparation for the journey begins, the characters express their ambitions and apprehensions, foreshadowing the trials they will face in their quest for exploration, survival, and the pursuit of scientific discovery under the relentless Northern skies. (This is an automatically generated summary.)
Release date is 2005-09-01
Produced by N. Wolcott
Keywords: Survival -- Fiction; Earthquakes -- Fiction; Fur traders -- Fiction; Northwest Territories -- Fiction